Selective inhibition of Sarcocystis neurona calcium-dependent protein kinase 1 for equine protozoal myeloencephalitis therapy. Issue 13 (December 2016) - Ojo, Kayode K.; Dangoudoubiyam, Sriveny; Verma, Shiv K.; Scheele, Suzanne; DeRocher, Amy E.; Yeargan, Michelle; Choi, Ryan; Smith, Tess R.; Rivas, Kasey L.; Hulverson, Matthew A.; Barrett, Lynn K.; Fan, Erkang; et al.
Abstract : Graphical abstract: Highlights: Sarcocystis neurona ( Sn ) CDPK1 has an atypical small gatekeeper residue selectively inhibited by BKIs. Evidence is provided that shows Sn CDPK1 is a potential target for rational EPM drug development. Bumped kinase inhibitors interfered with an early step in S. neurona tachyzoite host cell invasion. Nine of 10 mice in a BKI-1553 experimentally treated group were cured of equine protozoal myeloencephalitis. Abstract: Sarcocystis neurona is the most frequent cause of equine protozoal myeloencephalitis, a debilitating neurological disease of horses that can be difficult to treat. We identified Sn CDPK1, the S. neurona homologue of calcium-dependent protein kinase 1 (CDPK1), a validated drug target in Toxoplasma gondii . Sn CDPK1 shares the glycine "gatekeeper" residue of the well-characterized T. gondii enzyme, which allows the latter to be targeted by bumped kinase inhibitors. This study presents detailed molecular and phenotypic evidence that Sn CDPK1 can be targeted for rational drug development. Recombinant Sn CDPK1 was tested against four bumped kinase inhibitors shown to potently inhibit both T. gondii ( Tg ) CDPK1 and T. gondii tachyzoite growth. Sn CDPK1 was inhibited by low nanomolar concentrations of these BKIs and S. neurona growth was inhibited at 40–120 nM concentrations . Thermal shift assays confirmed these bumped kinase inhibitors bind CDPK1 in S. neurona cell lysates. Treatment with bumped kinase inhibitors before or after invasion suggests that bumped kinase inhibitors interfere with S . neurona mammalian host cell invasion in the 0.5–2.5 μM range but interfere with intracellular division at 2.5 μM. In vivo proof-of-concept experiments were performed in a murine model of S. neurona infection. The experimental infected groups treated for 30 days with compound BKI-1553 ( n = 10 mice) had no signs of disease, while the infected control group had severe signs and symptoms of infection. Elevated antibody responses were found in 100% of control infected animals, but only 20% of BKI-1553 treated infected animals. Parasites were found in brain tissues of 100% of the control infected animals, but only in 10% of the BKI-1553 treated animals. The bumped kinase inhibitors used in these assays have been chemically optimized for potency, selectivity and pharmacokinetic properties, and hence are good candidates for treatment of equine protozoal myeloencephalitis.